HUBUNGAN ANTARA PEMANFAATAN JAMBAN DAN PEMANFAATAN AIR DENGAN ANGKA KEJADIAN DIARE DI DESA KRACAK KECAMATAN AJIBARANG KABUPATEN BANYUMAS - Wasis Eko Kurniawan; Diannike Putri (Universitas Harapan Bangsa Purwokerto, 2013)
Diarrhea is a bowel movement in which the stool is liquid or semi-liquid, in which its water content is more than 200 ml/24 hours. Health center 1 in Ajibarang with 2.440 incidence cases of diarrhea is a health center with the highest cases of diarrhea in Banyumas. Severalfactors which can affect the incidence of diarrhea include the latrines andwater utilization. The purpose of this study is to determine the relationship between the utilization of latrines and water with the incidence of diarrhea in theVillage of Kracak Ajibarang in 2013. The number of samples were 72respondents, 36 patients suffered from diarrhea and 36 didn’t. The design ofthis study was explanatory research with case-control approach. The analysis of the data used univariate, bivariate analyzes (Chi Square),and multivariate analysis. The results show that Diarrhea sofferers in the village of Kracak whoused clean latrines were 20 respondents (55.56%), and those who used cleanwater and didn’t suffer from diarrhea were 25 respondents (69.44%). Fromthe relationship test, the p value of latrines utilization variable is 0.056 >0.05, and p value of water utilization is 0.250 > 0.05. It indicates that there is no significant relationship between the utilization of latrines and theutilization of water with the incidence rate of diarrhea in the Village ofKracak, Ajibarang 2012, the utilization of latrines has its significant valuesig. = 0.813 > 0.05, and the utilization of water has its significant value sig.= 0.617 > 0.05. In conclusion there is no association between the utilizationof latrines and the utilization of water with the incidence rate of diarrhea in the Village of Kracak, Ajibarang.Key Words : Diarrhea, water, latrines